Prolínání náboženské a sekulární perspektivy v rámci chorvatského feministického hnutí na příkladu práva na potrat - Ludmila Böhmová (Lidé Města)
The research shows that on the issue of abortion, the Croa-tian feminist movement, both secular and religious, agrees that it is an individual woman’s choice that should not be moralized and evaluated, and that the right to abortion should remain to be protected. Religious feminists use predominantly secular arguments for the right to abortion regardless of their relationship to religion or their personal religious identity. The transfer of arguments and narratives used across secular and religious actors supports the existing critiques of the dichotomy between the secular and the religious. The study views the scrutinized feminist movement through the perspective of the social networks existing between religious and secular feminists. The research shows that their interrelationships lead to the expansion of the boundaries of the shared collective identity of the studied feminist movement and to an increase in the mobilizing potential by incorporating the religious experience of women from religious communities. The research is grounded in the social movement theory, specifically in qualitative social network analysis and the content analysis of 16 semistructured interviews with actors of the Croatian feminist movement conducted between 2020–24, with a focus on their relationship to religion.